Structure-Property-Activity Relationship of Phenolic Acids and Derivatives. Protocatechuic Acid Alkyl Esters - Bruno Reis (2010)
The esterification of hydrophilic phenolic antioxidants is an efficient approach to enhance their solubility in apolar media. Herein, structure property studies on the antiradical activity of a series of protocatechuic acid alkyl esters have been accomplished. The increase of the lipophilicity was shown to significantly improve the antioxidant activity of protocatechuic esters. Their efficiency as radical scavengers was evaluated using distinctive analytical methods, namely, 2,2-diphenyl-1-picrylhydrazyl (DPPH) UV/visible method, electrochemistry, and differential scanning calorimetry. All the new alkyl protocatechuate antioxidants studied possessed better radical-scavenging capacity than the natural antioxidant protocatechuic acid. This work has shown that the alkyl ester side chain markedly influences the lipophilicity of this type of phenolic system without disturbing the core of the molecule responsible for antioxidant activity. The data on the antioxidant activity obtained using the different analytical methods correlated well with each other and have revealed the interesting antioxidant potential of alkyl esters of protocatechuic acid.